Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1086/519790
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Bursts of Coherent Radio Emission from an Ultracool Dwarf

Abstract: We report the detection of periodic (p = 1.96 hours) bursts of extremely bright, 100% circularly polarized, coherent radio emission from the M9 dwarf TVLM 513-46546. Simultaneous photometric monitoring observations have established this periodicity to be the rotation period of the dwarf. These bursts, which were not present in previous observations of this target, confirm that ultracool dwarfs can generate persistent levels of broadband, coherent radio emission, associated with the presence of kG magnetic fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
303
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 220 publications
(341 citation statements)
references
References 27 publications
33
303
4
1
Order By: Relevance
“…From previous observations we know that the rotation period is ≈1.96 h (Hallinan et al 2006;Lane et al 2007). The main difference between the present data and the 2006 data reported by Hallinan et al (2007) is that the intervals of activity are longer, typically spread over 0.25 phase, comprising of several pulses. For the June 2007 data shown in Fig.…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…From previous observations we know that the rotation period is ≈1.96 h (Hallinan et al 2006;Lane et al 2007). The main difference between the present data and the 2006 data reported by Hallinan et al (2007) is that the intervals of activity are longer, typically spread over 0.25 phase, comprising of several pulses. For the June 2007 data shown in Fig.…”
Section: Resultscontrasting
confidence: 88%
“…In addition, we have an inter-pulse at ≈3.8 h (best seen in Stokes I but also visible in Stokes V), i.e. 0.5 phase later than the pulse at ≈2.8 h. As shown by Hallinan et al (2007), due to the beaming of the ECM emission, additional activity can be observed ≈0.5 phase later. However, depending on the local density condition, this secondary activity 0.5 phase later is not always observed.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…By contrast, brown dwarfs are very bright radio emitters, but no correlation between X-ray and radio emission exists as is established for stars and solar events (Güdel-Benz relation, Benz and Güdel 1994). Since the discovery of the first radio emitting brown dwarf by Berger et al (2001), numerous surveys have detected radio emission at GHz frequencies in nearly 200 objects (Berger 2002(Berger , 2006Berger et al 2010;Hallinan et al 2006Hallinan et al , 2007Hallinan et al , 2008McLean et al 2012), including emission in the coolest brown dwarfs with spectral types as late as T6.5 (Route and Wolszczan 2012). In twelve of these objects, the radio emission is highly polarised, coherent and pulses on the rotation period of the dwarf.…”
Section: Multi-wavelength Observations Of Activity On Ultracool Dwarfsmentioning
confidence: 99%
“…In five of these systems, WD0137-349B (Maxted et al 2006), NLTT5306 (Steele et al 2013), SDSS141126þ200911 (Beuermann et al 2013), WD0837þ185 (Casewell et al 2012) and GD1400B (Farihi and Christopher 2004), the brown dwarf is known to have survived a phase of common envelope Fig. 13 Light curves of the total intensity (Stokes I) and the circularly polarised (Stokes V) radio emission detected at 8.44 GHz from TVLM 513-46546, an M9.5 dwarf, taken from Hallinan et al (2007). Right circular polarisation is represented by positive values, and left circular polarisation is represented by negative values in the Stokes V light curve.…”
Section: Multi-wavelength Observations Of Activity On Ultracool Dwarfsmentioning
confidence: 99%